Offline CAD-based Robot Programming and Welding Parametrization of a Flexible and Adaptive Robotic Cell Using Enriched CAD/CAM System for Shipbuilding - Ferreira, L. Alonso; Figueira, Y. Lapido; Iglesias, I. Fernández; Souto, M. Álvarez (Procedia manufacturing, 2017)
Shipbuilding continues to be a handwork process, where many shipyard's facilities are poorly optimized, and there is not flexibility enough for more complex manufacturing techniques. In order to provide solutions, shipbuilding sector is emerging with the purpose of dinamizing its R&D environment, developing advanced tools to make easier the technological evolution of the sector. The proposed solution is a hyper-flexible welding robotic cell with 9 degrees of freedom (6 axes robot arm unit mounted on a 3 axes XYZ gantry) adapted to small batch manufacturing. The cell is programmed in a CAD (Computer Aided Design) environment allows to implement automatic welding sequences to an inexperienced programmer: ‘Offline automatic system programming’.